Food worry and mental health outcomes during the COVID-19 pandemic - Brenna B. Han; Eva Purkey; Colleen M. Davison; Autumn Watson; Dionne Nolan; Dan Mitchell; Sheldon Traviss; Jennifer Kehoe; Imaan Bayoumi (BMC, 2022)
Abstract Background There is limited and inconsistent literature examining the relationship between food worry and mental health in the context of the COVID-19 pandemic. This study examined the association between food worry and mental health among community dwelling Canadian adults during the COVID-19 pandemic. Methods Adults age 16 years and older completed an anonymous online questionnaire between April 1, 2020 and November 30 2020. Measures of pre-pandemic and current food worry, depression (PHQ-2), anxiety (GAD-2), and sociodemographic variables were included. Multivariable logistic regression models were used to determine the association between food worry and symptoms of depression and anxiety. Results In total, 1605 participants were included in analyses. Worry about affording food was reported by 320 (14.78%) participants. In models adjusting for sociodemographic covariates, compared with people without food worry, participants who had food worry were 2.07 times more likely to report anxiety symptoms (aOR 2.07, 95% CI: 1.43 - 2.98, p < .001) and were 1.9 times more likely to report depressive symptoms (aOR 1.89, 95% CI: 1.39-2.57, p < .0001). Lower income, lower education, and pre-existing mental health conditions were significant predictors of symptoms of depression. Female gender, younger age, lower education, lower income, and pre-existing mental health condition were significant predictors of anxiety symptoms. Conclusion Our study highlights the relationship between food worry and poor mental health. Policy supports such as improved income supports, clinical implications such as screening for food worry in primary care, referral to emergency food programs and support with meal planning may help mitigate mental health symptoms during the current pandemic, during future societal recovery from this pandemic and during future pandemics.